A new species of lizard genus Enyalius (Squamata, Leiosauridae) from the highlands of Chapada Diamantina, state of Bahia, Brazil, with a key to species - Rodrigues, Miguel Trefaut; Freitas, Marco Antonio de; Silva, Thais Figueiredo Santos; Bertolotto, Carolina Elena Viña (Phyllomedusa: Journal of Herpetology, 2006)
A new species of lizard genus Enyalius is described from Fazenda Caraibas, municipality of Mucugê, state of Bahia, northeastern Brazil, in the northern portion of the Serra do Espinhaço. It is characterized by an almost straight canthal ridge, a distinctive enlarged subocular, ventral scales and infradigital lamellae smooth, tail length varying between 2.02-2.18 times snout-vent length, 54-63 vertebral scales between occiput and base of tail, 144-167 paravertebral scales between occiput and base of tail, 44-47 transverse rows of ventrals between posterior level of forelimbs and anterior level of hindlimbs, 52-66 scales at mid-body between middle of venter and crest, 17-18 and 25-28 infradigital lamellae, respectively under Finger IV and Toe IV, 23-27 scales along dorsal surface of tibia, and 33-40 gular scales between mental and collar. The new species is sexually dichromatic with males being brightly colored with a series of six very conspicuous transverse wide black dorsal bands on body separated by deep orange light areas and females dull colored with a pattern of irregular dark or light brown longitudinal stripes. The new species was obtained at Serra do Sincorá, state of Bahia, Brazil, in low, thin, and dense semidecidual forests situated around 1000m altitude, near the headwaters of the Rio Paraguaçu. Character distribution in Enyalius is discussed, the presently recognized subspecies of Enyalius catenatus are elevated to full species status and a key to the current species of Enyalius is presented.